2000
DOI: 10.1523/jneurosci.20-22-08290.2000
|View full text |Cite
|
Sign up to set email alerts
|

Associative Long-Term Depression in the Hippocampus Is Dependent on Postsynaptic N-Type Ca2+Channels

Abstract: Long-term depression (LTD) is a form of synaptic plasticity that can be induced either by low-frequency stimulation of presynaptic fibers or in an associative manner by asynchronous pairing of presynaptic and postsynaptic activity. We investigated the induction mechanisms of associative LTD in CA1 pyramidal neurons of the hippocampus using whole-cell patch-clamp recordings and Ca 2ϩ imaging in acute brain slices. Asynchronous pairing of postsynaptic action potentials with EPSPs evoked with a delay of 20 msec i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 49 publications
4
61
2
Order By: Relevance
“…Prolonged low-frequency synaptic stimulation or asynchronous pairing of EPSPs and action potentials in the hippocampus leads to both NMDAR and mGluR activation (Oliet et al, 1997;Normann et al, 2000). Our results suggest that although both receptors can contribute to the depression of EPSPs, only mGluR activation is necessary for activity-dependent decreases in I h .…”
Section: Mechanismmentioning
confidence: 63%
See 1 more Smart Citation
“…Prolonged low-frequency synaptic stimulation or asynchronous pairing of EPSPs and action potentials in the hippocampus leads to both NMDAR and mGluR activation (Oliet et al, 1997;Normann et al, 2000). Our results suggest that although both receptors can contribute to the depression of EPSPs, only mGluR activation is necessary for activity-dependent decreases in I h .…”
Section: Mechanismmentioning
confidence: 63%
“…Hippocampal LTD requires the activation of either NMDA receptors (NMDARs) (Dudek and Bear, 1992;Mulkey and Malenka, 1992;Bliss and Collingridge, 1993;Christie et al, 1996;Oliet et al, 1997;Malenka and Bear, 2004) and/or metabotropic glutamate receptors (mGluRs) (Bolshakov and Siegelbaum, 1994;Selig et al, 1995;Oliet et al, 1997;Huber et al, 2000;Normann et al, 2000;Rammes et al, 2003). We previously described a role for NMDA receptors in the plasticity of h-channels during LTP (Fan et al, 2005).…”
Section: Increased Excitability Requires Mglur Activationmentioning
confidence: 99%
“…A different explanation may be that low 5-HT has been shown to induce long-term depression (LTD), as opposed to long-term potentiation (LTP) of synaptic plasticity, especially in hippocampal area, possibly through modulation of calcium (2ϩ) channels, through which 5-HT has been shown to normally inhibit LTD (Normann 2000;Normann et al 2000). This mechanism may account for positive effects of 5-HT in patients and may also explain tryptophan-depletion induced memory consolidation impairment and mood lowering in normal subjects (Riedel et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the N-type Ca 2+ channel has been shown to be the cellular target of ATP/ADP neuromodulation in cells of the dorsal root ganglions . Very interestingly, Normann et al (2000) found these channels are involved in a form of hippocampal LTD with similar associative properties to prefrontal LTD. The dependence of LTD on N-type Ca 2+ channels provides a precise way of gaining control on LTD.…”
Section: Mechanism Of P2y 1 Blockade Of Ltdmentioning
confidence: 92%
“…Because this mechanism is important in the search for a possible ATP modulation of LTD, we tested further wheter not a toxin, but a neuromodulator acting on N-type Ca 2+ channels could have the same effect on LTD. In this respect, we tested the selective agonist of the 5-HT 1A receptor OH-DPAT (1 µM), which is known to inhibit N-type Ca 2+ channels in a membrane delimited way via G i/o activation (Foehring, 1996), and to prevent LTD induction via the same mechanism (Normann et al, 2000). As we anticipated, OH-DPAT avoided prefrontal LTD (figure 3.6B).…”
Section: Contribution Of Vsccsmentioning
confidence: 96%